2023
DOI: 10.3390/jcm12206573
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of Activation Markers CD25 and CD69 Increases during Biologic Treatment of Psoriasis

Michał Adamczyk,
Joanna Bartosińska,
Dorota Raczkiewicz
et al.

Abstract: CD (cluster of differentiation) 69 and CD25 are considered early and late markers of the activation of lymphocytes, respectively. CD25 is a part of the IL-2 receptor and is present on the surface of immune and non-immune cells, with high amounts on activated lymphocytes and regulatory T cells. CD69 is expressed on various types of white blood cells, including newly activated lymphocytes, lymphocytes infiltrating tissues isolated from subjects with chronic auto-inflammatory diseases, several subtypes of memory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…CD25 plays a dual role as a regulatory T cell marker as well as an activation T cell marker. While being highly expressed on Tregs, CD25 expression on T cells, in general, indicates immune activation and has been associated with autoimmune diseases [28,29,42]. Following this, we found that increased CD25 expression was exclusive to non-Tregs and not in the Tregs subset of CD8 + T cells.…”
Section: Discussionsupporting
confidence: 67%
“…CD25 plays a dual role as a regulatory T cell marker as well as an activation T cell marker. While being highly expressed on Tregs, CD25 expression on T cells, in general, indicates immune activation and has been associated with autoimmune diseases [28,29,42]. Following this, we found that increased CD25 expression was exclusive to non-Tregs and not in the Tregs subset of CD8 + T cells.…”
Section: Discussionsupporting
confidence: 67%
“…To monitor the level of activation, activation-induced markers were used: CD25 for the first panel or HLA-DR for the second panel. CD25 is part of the IL-2 receptor complex and highly expressed in activated circulating immune cells and Tregs ( 36 ). In contrast, HLA-DR is expressed constitutively by B-cells and monocytes, albeit its expression is upregulated in response to stimulation by CpG (ODN2006) in B-cells or by LPS in monocytes ( 37 , 38 ).…”
Section: Introductionmentioning
confidence: 99%